The effect of alar release on interalar changes in Le Fort I osteotomy - Behnam Bohluli; Neda Afsar; Ali Bakhshandeh-Fard; Mahsa Shariati (Journal of Craniomaxillofacial Research, 2015)
Introduction: Due to the increase in Le Fort surgeries and its effect on nose widening, it seems necessary to use an alternative method without this effect. The present research examined the effect of alar release on interalar changes in Le Fort I osteotomy.